Guava: phytochemical composition of a potential source of antioxidants for cosmetic and/or dermatological applications - Bruna Galdorfini Chiari-Andréo; Eliane Trovatti; Joana Marto; Maria Gabriela José de Almeida-Cincotto; Ana Melero; Marcos Antonio Corrêa; Leila Aparecida Chiavacci; Helena Ribeiro; Teresa Garrigues; Vera Lucia Borges Isaac (Universidade de São Paulo, 2017)
ABSTRACT Guava (Psidium guajava L.) is a native fruit of the American tropics with commercial applications for its taste, flavor and aroma. Numerous pharmacological uses have been described for it, such as the antiseptic effect of its leaves, the use of the fresh fruit and tea from its leaves for the treatment of diarrhea, dysentery, diabetes mellitus, and others. However, considering its rich composition, the guava also is a potential source of antioxidants to be used in the development of new formulations for cosmetic and/or dermatological applications, the main focus of this research. Herein, we describe the study of the phytochemical composition and the antioxidant activity of a guava extract prepared with non-toxic solvents aiming its use at biological applications. High performance liquid chromatography and mass spectrometry were employed to identify the major components, while thermoanalytical measurements and hot stage microscopy were used to assess the chemical stability of guava fruit extract. The antioxidant activity was also evaluated assessing the SOD-like activity and ABTS free radical scavenger. The results show that the extract is a rich source of phenolic compounds, such as quercetin, kaempferol, schottenol, among many others. All of the components found in guava extract exhibit biological effects according to the literature data, mainly antioxidant properties.